2020
DOI: 10.3389/fped.2020.572633
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Isolated From Infant Feces Inhibits Toxigenic Clostridioides (Clostridium) difficile

Abstract: Clostridioides (Clostridium) difficile infection is implicated as a major cause of antibiotic-associated diarrhea in hospitals worldwide. Probiotics, especially lactic acid bacteria, are the most frequently used alternative treatment. This study aims to identify potential probiotic enterococci strains that act against C. difficile strains and exert a protective effect on colon adenocarcinoma cells (HT-29 cells). To this end, nine Enterococcus strains isolated from the feces of breast-fed infants were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Interestingly, Rada et al found that both the Clostridia and Bifidobacteria in the feces of infant (3-253Radadays old) grow vigorously on the prebiotic oligosaccharides, which may pose a challenge for supplementing prebiotics to infant lacking Bifidobacteria (144). In contrast, Enterococcus faecalis isolated from infant feces can inhibit the growth of Clostridium difficile, which may have potential applications for preventing Clostridium difficile colonization and infection (145). In short, in early life, we need to beware of Clostridium to prevent them from becoming the dominant species in infant gut microbiota.…”
Section: The Genus Clostridiummentioning
confidence: 99%
“…Interestingly, Rada et al found that both the Clostridia and Bifidobacteria in the feces of infant (3-253Radadays old) grow vigorously on the prebiotic oligosaccharides, which may pose a challenge for supplementing prebiotics to infant lacking Bifidobacteria (144). In contrast, Enterococcus faecalis isolated from infant feces can inhibit the growth of Clostridium difficile, which may have potential applications for preventing Clostridium difficile colonization and infection (145). In short, in early life, we need to beware of Clostridium to prevent them from becoming the dominant species in infant gut microbiota.…”
Section: The Genus Clostridiummentioning
confidence: 99%
“…Thus, the anti-spore germination activity might be facilitated by the action of BSH enzymes. Romyasamit et al, 2020, also found that E. faecalis PK 1201 probiotics can produce BSH enzymes, which break down bile salt and are further implicated in the decline of C. difficile spore development 10 . In this study, the BSH enzymes might secrete out into the CFS used to prepare LCFS that shows anti-spore germination activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a resistance to vancomycin has emerged in this genus [ 102 , 105 ]. Romyasamit et al (2020) exhibited that six E. faecalis strains have a probiotic effect and anti- C. difficile activity [ 106 ]. Klebsiella pneumonae is present in the mucus layer with C. difficile [ 107 ].…”
Section: Discussionmentioning
confidence: 99%